Level IIb involvement in oral cavity squamous cell carcinoma - Patni, Parth; Dalmia, Deepak; Davange, Narsinha; Bhagavan, Karthika; Palwade, Amit; Goyal, Rizul (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Cervical lymph node status is the most significant prognostic factor in the treatment of patients with OSCC. Adequate clearance of level IIb lymph nodes require traction and elevation of the spinal accessory nerve (SAN) and can lead to consequent shoulder problems.Therefore, avoiding the dissection of level IIb has been increasingly proposed to overcome this complication. The aim of this study was to determine the prevalence of level IIb metastasis in patients with oral squamous cell carcinomas (OSCCs). Methods: A total of 106 newly diagnosed oral cavity cancer patients requiring surgery as the primary modality were included in the study. Preoperative clinical examinations were done and tumor-node-metastasis staging was noted. Intraoperative, level IIb nodal tissue was dissected and sent separately. Results: A total of 106 neck dissections were done out of which male: female ratio of 2.78:1. 49.05% patients were suffering from buccal mucosa carcinoma followed by tongue carcinoma (22.64%). 52.83% of patients had no neck involvement. Among neck positive cases, pN1 was the most common presentation. Out of these, only 8 (7.54%) neck dissections had level IIb positive. Conclusions: Dissection of the level IIb region in patients with OSCC may be required only in cases with advanced N stage, positive level IIa lymph nodes, and extra capsular spread. Further evaluation can be done among various subsites of OSCC, clinical staging of tumour, occult bilateral nodal metastasis to assess the need of resection of level IIb in OSCC.